Minimum wage: Global challenges and perspectives - Sergei Soares (International Policy Centre for Inclusive Growth (IPC-IG), 2018)
The increase in inequality over the last few decades in most of the world has been a constant source of concern for policymakers and analysts. Inequality can hinder economic growth, reduce well-being and increase poverty. It also fuels social unrest and reduces social cohesion. Great attention has been given to the role of fiscal redistribution (or lack thereof) in the inequality debate, but perhaps mechanisms that involve money passing directly from one economic agent to another, rather than through the hands of the State, deserve more attention. In a time of weakened labour unions and decreasing income mobility, can the minimum wage once again shine as a market-friendly and effective policy tool? [...]
Keywords: 330; Minimum; wage; global; challenges; perspectives